Formation of Professional Competencies in Students-ecologists as a Psychological and Pedagogical Problem - Maksymenko, Nadiya; Korobkova, Hanna; Kyrpychova, Iryna; Cherkashyna, Nadiia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The purpose of the study is to assess the compliance of professional competencies of graduates – environmentalists with the needs of the labor market. The work is based on the results analysis of a sociological survey conducted among graduates and stakeholders. The authors conducted a survey of graduates and their potential employers on their priorities among the professional competencies. The authors have analyzed professional opportunities of graduates-ecologists and the employers’ requirements related to their competencies. In this regard, we calculated a rating of competencies significance for employers. The article compares professional expectations of the graduates and their employers. Conclusions. The authors conclude that students attach great importance to competencies, providing opportunities for professional growth, mastery of new technologies and application of innovations. Employers bring teamwork skills, professional skills and knowledge in the professional sphere to the fore.
Keywords: ecologist; competence; educational process; profession; polls